A tradução de L'enfant de sable, de Tahar Ben Jelloun, no Brasil: uma proposta de glossário para O menino de areia - Colares, Adriana Almeida (2019)
The act of translating is a very old activity. The act of reflecting and critically analyzing the translations also refers to periods far in Translation History, it goes back to Cicero (46 BC). Since then, the theoretical views on the translation act are directed towards the dual issue of foreignized or domesticated translation. In the twentieth century, a functionalist approach brings other looks to the translation and duality that has always prevailed in the theories gave way to translation as purpose. According to this approach, the translation is seen as something that is not a responsibility for the translator. Translating a literary work, for example, involves countless other factors that go beyond sourcing the text from one language to another. Therefore, the purpose of this work is to trace a historical course of the translational thought concerning to the critical approach. We begin with Cicero, passing through the foreign and domestic duality through history and we arrive at the functionalist approach of translation, with the concepts presented by Christiane Nord in Translation as a purposeful activity. Functionalist approaches explained (2014). Then we will analyze the work O menino de areia by the Moroccan writer Tahar Ben Jelloun, translated into Portuguese and published in Brazil in 1986. The reflections will be based on the concepts of translation as function, the functionalist approach, emphasizing the role of the paratexts that go along a translated work, emphasizing its role in the insertion of the literary work in the culture of arrival. Finally, we will propose a glossary of cultural and religious terms taken from the mentioned literary work, since this is a textual accompaniment that assists in the insertion of the work in the literary universe of arrival and in the fulfillment of one of the functions of translation, which is the diffusion cultural. We conclude, therefore, that to critically analyze a translation goes beyond the textual element spilled from one language to another, one must consider the paratextual elements and the different circumstances that involve the translation process, from the choice of the text to be translated, until the moment it reaches the audience to whom the text is addressed.